COVID‐19: Knowledge, anxiety, academic concerns and preventative behaviours among Australian and Indian undergraduate nursing students: A cross‐sectional study. Issue 5 (26th January 2021) - Kochuvilayil, Terese; Fernandez, Ritin S.; Moxham, Lorna J.; Lord, Heidi; Alomari, Albara; Hunt, Leanne; Middleton, Rebekkah; Halcomb, Elizabeth J.
Abstract: Aims and Objectives: To compare knowledge, anxiety, academic concerns and preventative behaviours between undergraduate nursing students in Australia and India during the COVID‐19 pandemic. Background: Based on the World Health Organization's direction for containment of the novel coronavirus (COVID‐19), countries implemented varying levels of restrictions including closure of university campuses and providing on line undergraduate education. Methods: Students in NSW, Australia and Kerala, India completed an online survey assessing their (a) knowledge and source of information about COVID‐19; (b) anxiety; and coping strategies; (c) academic concerns; and (d) preventative behaviours. Descriptive and inferential statistics were used to summarise the data. Results: Data from 99 Australian and 113 Indian undergraduate nurses were analysed. Greater number of Indian students indicated having sufficient knowledge of COVID‐19 (OR 0.22; 95% CI 0.08, 0.63), getting information about COVID‐19 from social media (OR 0.03; 95% CI 0.01, 0.07) and being concerned about 'attending clinical placement' (MD‐1.08; 95% CI −1.94, −0.23). Australian students reported significantly higher levels of anxiety (MD 1.99 95% CI 1.21, 2.78), difficulty sleeping (OR 18.00; 95% CI 6.76, 47.96), concentrating (OR 33.22; 95% CI 13.85, 79.67) and eating (OR 14.05; 95% CI 3.19, 61.84). Greater number of Australian students indicated that they would go to the University if they needed to meet with other students (OR 9.21; 95% CI 3.08, 27.55), had to access the library (OR 7.20; 95% CI 3.26, 15.90) or had a group assignment (OR 2.93; 95% CI 1.26, 6.77). Conclusions: Wide variations were present in knowledge, anxiety, academic concerns and preventative behaviours among undergraduate nursing students in two countries. Relevance to clinical practice: Undergraduate students may benefit from additional support from the University and staff in the clinical setting with online learning and resources in order to adjust to the 'new normal' and enable them to achieve academic success.